Geographical Potential of Sumedang Regency Towards Paragliding Sport - Januar Riyadi; Rizal Ahmad Fauzi; Encep Sudirjo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Sumedang Regency which based on geographical conditions is located on a plateau and has many hills so that it can support tourists to do Paragliding sports. Paragliding sports venues in Sumedang Regency consist of three places and have different heights. Toga Village has a height of 200 m from the landing site and has a Launch to Landing  Distance of 900, for Batu Dua which is 500 m high from the landing site and has a Launch to Landing  Distance of 2610 m, while Buricak Burinong Hill which is 195 m high from the landing site and has a Launch to Landing Distancei.e. 900 m. The three places both have their own beauty, even becoming a strategic place in doing paragliding. The beginning of the emergence of Paragliding is inseparable from the emergence of a sense of desire to be able to fly enjoying the scenery of the wild and arrive at the achievements achieved. The purpose of this study is to see the geographical potential of tourism through paragliding in Sumedang Regency and also to find out the reasons why the interest of the people of Sumedang Regency to participate in paragliding is still minimal. Sumedang Regency has several destinations to do paragliding, one of which is in Toga Village. Toga Village, located in Sumedang Regency, offers an enchanting natural panorama.  The research method used is a qualitative method with a descriptive research design in the form of interviews, observations and documentation. Based on the results of research that the good geographical potential of Sumedang Regency for Paragliding sports can be seen from the beauty, place, height and minimal natural disasters and accidents, so that Sumedang Regency is a suitable place to be used for Paragliding sports.